2021
DOI: 10.1016/j.psj.2021.101038
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the tongue in the domestic turkey (Meleagris gallopavo gallopavo var. domesticus)

Abstract: Nowadays, microstructural and ultrastructural analysis of organs of the avian beak cavity points to new aspects of adaptation to food intake through the various feeding groups. These data should undoubtedly be considered in the time of mass production of compound feed in poultry, when many studies analyze the optimal size of food particles and their doses. Galliformes possess complex mechanisms of food collection and transport in the beak cavity. They collect food by pecking and transport food by using catch-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…This is important for a constantly desquamating parakeratinized epithelium. During the cytodifferentiation of the keratinocytes in the ortho- and parakeratinized epithelium of the avian tongue, cells in the intermediate layer change their shape [ 34 , 35 , 36 , 37 , 38 , 39 ]. Firstly, they become polygonal and then flatten.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is important for a constantly desquamating parakeratinized epithelium. During the cytodifferentiation of the keratinocytes in the ortho- and parakeratinized epithelium of the avian tongue, cells in the intermediate layer change their shape [ 34 , 35 , 36 , 37 , 38 , 39 ]. Firstly, they become polygonal and then flatten.…”
Section: Discussionmentioning
confidence: 99%
“…The cornified layer, which is the final product of the cornification process of the multilayered epithelia, in the orthokeratinized epithelium is built up by strongly flattened keratinocytes devoid of cell nuclei and organelles [ 34 , 35 , 36 , 37 , 38 , 39 ]. The superficial cells of the orthokeratinized epithelium exfoliate as scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological and functional tongue characteristics differ significantly among tetrapods. Several studies have reported high lingual papillae densities on the surface of reptilian tongues (Beisser et al, 1998; Cizek et al, 2019; Iwasaki, 1990; Iwasaki et al, 1992; Lintner et al, 2012), similarly to amphibians (Jasiflski, 1979; Żuwała & Jakubowski, 2001), birds (Abumandour & El‐Bakary, 2017; Jackowiak et al, 2011; Skieresz‐Szewczyk et al, 2021) and mammals (Barbosa et al, 2020; Barboza & Larkin, 2020; Ciena et al, 2013; Masuko et al, 2007; Okada & Schraufnagel, 2005; Reginato et al, 2020). Only snakes are currently known to lack lingual papillae on the entire tongue surface (El‐Mansi et al, 2020; Iwasaki & Kumakura, 1994; Iwasaki & Yoshihara, 2003).…”
Section: Discussionmentioning
confidence: 99%